Incorporating personal experience in free-choice environmental learning: lessons from a zoological theme park. Issue 8 (3rd August 2019) - Huang, Xiaoting; Loo, Becky P. Y.; Zhao, Ying; Chow, Alice S. Y.
Abstract: Conservation education can be fostered through formal and informal learning. An increasing number of zoological facilities with conservation missions have provided experiential learning venues characterized by self-directed, self-motivated and diversified learning experience integrated with fun and entertainment. In this paper, we develop an emotion–time–space model to address the diversity in visitors' experience and its influence on conservation intentions. An empirical study at Ocean Park, Hong Kong indicated that visitor's emotions, temporal and spatial behaviour influence the effectiveness of conservation education. Changes of personal emotions during the entire visit, the sequence of stops made, and the nature and combinations of attractions visited matter in explaining stronger intentions to protect animals and the environment. These findings have implications for zoological theme park design and improvements of learning outcomes in a free-choice learning environment.